2021
DOI: 10.3390/pr9020223
|View full text |Cite
|
Sign up to set email alerts
|

Apple Fermented Products: An Overview of Technology, Properties and Health Effects

Abstract: As an easily adapted culture, with overloaded production in some parts of the globe, apples and their by-products are being redirected to pharmaceutical, canning and beverages industries, both alcoholic and non-alcoholic. Fermentation is generally considered to increase the bioavailability of bioactive compounds found in apple, by impacting, through a high degree of changes, the product’s properties, including composition and health-promoting attributes, as well as their sensory profile. Probiotic apple bevera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 232 publications
(277 reference statements)
1
32
0
1
Order By: Relevance
“…Then, by selecting the appropriate keywords, the following scientific databases were searched: Web of Science, Science Direct, Scopus and PubMed. For each of the read publications, certain principles were established for their inclusion in this review [ 16 , 17 ]. The most up-to-date scientific articles and those that best suited the issues of the review were selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, by selecting the appropriate keywords, the following scientific databases were searched: Web of Science, Science Direct, Scopus and PubMed. For each of the read publications, certain principles were established for their inclusion in this review [ 16 , 17 ]. The most up-to-date scientific articles and those that best suited the issues of the review were selected.…”
Section: Methodsmentioning
confidence: 99%
“…At the initial stage of preparing this review, similarly to Guiné et al (2020) and Guiné et al (2021), the topic to be addressed was selected [16,17]. After searching available literature, it was concluded that there is a need to gather in a review article up-to-date information on the importance of sheep's milk bioactive substances on human health, which is scattered around the scientific literature.…”
Section: Methodsmentioning
confidence: 99%
“…en, after selecting suitable keywords, the review was structured into different sections as follows [12][13][14]:…”
Section: Methodsmentioning
confidence: 99%
“…Fermentation for 8 days at 20°C resulted in the drop of the bacterial count below the detection limit, making the fermented juice safe to drink. Moreover, LAB-fermented products, like cider obtained from the fermentation of apple juice, have a high content of acids, resulting in pH decrease, which prevents the growth of patogenic bacteria [Guiné et al, 2021]. Contrary, the study with cauliflower subjected to the spontaneous fermentation and spiked with Listeria monocytogenes and Salmonella typhimurium showed that LAB were not able to compete with pathogenic bacteria present in the cauliflower until the end of fermentation [Paramithiotis et al, 2012].…”
Section: Safetymentioning
confidence: 98%